On the Exploitation of Mid-infrared Iridescence of Plumage for Remote Classification of Nocturnal Migrating Birds. Issue 5 (May 2013) - Brydegaard, Mikkel; Samuelsson, Per; Kudenov, Michael W.; Svanberg, Sune
A challenging task in ornithology lies in identifying high-altitude nocturnal migrating bird species and genders. While the current approaches including radar, lunar obscuration, and single-band thermal imaging provide means of detection, a more detailed spectral or polarimetric analysis of light has the potential for retrieval of additional information whereby the species and sex could be determined. In this paper, we explore remote classification opportunities provided by iridescent features within feathers in the mid-infrared region. Our approach first involves characterizing the microstructural features of the feather by using rotation and straining, and a scheme for their remote detection is proposed by correlating these microstructural changes to spectral and polarimetric effects. Furthermore, we simulate the spectral signature of the entire bird by using a model that demonstrates how classification would be achieved. Finally, we apply infrared hyperspectral polarization imaging, showing that the net iridescent effect persists for the bird as a whole.